Lipid specificity in the interaction of cytochrome c with anionic phospholipid bilayers revealed by solid-state 31P NMR. - Pinheiro, T; Watts, A (1994)
Phosphorus-31 NMR has been used to investigate the interaction of cytochrome c with bilayers of the anionic lipids dioleoylphosphatidylglycerol (DOPG), dioleoylphosphatidylserine (DOPS), and diacylphosphatidylinositol (diacylPI). All 31P NMR spectra revealed the typical line shapes characteristics of phospholipids in liquid-crystalline bilayers. The effects on the 31P chemical shift anisotropy (CSA) for each system reflect particular modes of phospholipid headgroup interaction with cytochrome c. A distinct increase in the CSA for DOPS bilayers was observed upon binding of cytochrome c, which is likely to arise from a partial restriction of the amplitude of motion on this phospholipid headgroup. 31P NMR spin-lattice (T1) relaxation times of the various phospholipid-cytochrome c complexes show that conformational changes occur in the protein on binding to anionic phospholipids. These protein conformational changes are observed through paramagnetic enhancement of the measured 31P spin-lattice relaxation times for lipid phosphates. However, the 31P T1 values for the various complexes with cytochrome c show a different temperature dependence for each lipid, revealing different modes of protein interaction for each of the different lipid headgroups. The phosphate of DOPS was most efficiently relaxed by cytochrome c, while the relaxation of the phosphate in the PI headgroup was not affected. The relaxation profile for DOPG-bound cytochrome c shows a more complex behavior, where the lipid phosphorus relaxation is strongly enhanced above 15 degrees C, but not significantly affected at lower temperatures. It was found that the enhancement of lipid phosphorus relaxation is a result of the conformational changes in the protein, in which the heme becomes accessible to lipid phosphate upon binding to charged bilayer surfaces.(ABSTRACT TRUNCATED AT 250 WORDS)